Very Severe Hypertriglyceridemia in Children with Diabetic Ketoacidosis - Tiara Ella Sari; Eka Agustia Rini; Khairunnisa Khairunnisa (Universitas Syiah Kuala, 2021)
Background: Hypertriglyceridemia can be observed in up to 50% of patients with diabetic ketoacidosis (DKA), but a condition for DKA with very severe hypertriglyceridemia is uncommon. The objective of this case report is to present and describe the clinical features, laboratory investigations, case management, and natural course of hypertriglyceridemia in DKACase summary: A 9-year-old girl referred by district hospital with DKA and hypertriglyceridemia. Chief complaint was a decreased in consciousness for 16 hours before the admission. Patient has been known to suffer from diabetes mellitus within these 9 months. At ER patient looked severely ill, GCS 7, Kussmaul breathing. Random blood glucose was 255 mg/dL. Glycosuria and ketone urine tests were positive. Triglyceride level was 16.200 mg/dL. She had diagnosed with diabetic encephalopathy, DKA and very severe hypertriglyceridemia due to DKA. We treat DKA with standard guidelines, and on the 15th day we gave additional therapy fibrates and omega oil to treat the very severe hypertriglyceridemia. The level of triglyceride decreased gradually with hydration and insulin in standard guideline for DKA but didn’t achieve the normal level. With additional treatment, normal level of triglyceride achieved without any clinical side effects.Conclusion: Triglyceride level should be monitored in DKA patients. The hypertriglyceridemia can be treated by hydration, insulin, fibrates, and omega oil. The use of these treatment need to be evaluated for side effects.